KAPITAL SOSIAL IKATAN WARGA SANIANGBAKA - OKTAVIA S.Sos, M.Si, DIAN ANGGRAINI (Jurnal Pelangi : Research of Education and Development, 2011)
Ties in the social structure and culture Saniangbaka society which denies its members have beenable to create a socio-economic forces in society as a whole Saniangbaka. The discussion in thisstudy focused on the Social Capital anchored in the social structure of Minangkabau society,namely in the form of organization Saniangbaka Residents in Jakarta. In discussing itinvestigated a). whether the social structure of Minangkabau culture influence the structure andorganization Saniangbaka Citizens Association (IWS) in Jakarta, b). whether the social structureand culture of Minangkabau and organizational structure will emerge capital di Jakarta IWSculturalcapital, c). and whether the cultural structures that emerged capital-capital culture.The study investigated using the framework of thinking about socio-cultural bonding structureSaniangbaka community about social capital as a value Mutual trust (trust) between members ofthe public against the leadership. Didefenisiakan Social Capital as a social institution involvingnetworks (Networks), norms (norms), and social trust (Social Trust) yangmendorong on a socialcollaboration (Coordination and cooperation) for the common good. (Putnam: 1993)Putnam (1993b: 3) also noticed that the social structure in the form of networks "CivicEngagemnent" to facilitate coordination and communication, and cooperation, the party of massgatherings, sporting groups, and other associations. Describe the interaction of intensehorizontal. Because it is hypothetical Putnam (1993a: 173) states increasingly dense networkswithin the community, the more likely people work together to benefit the community, the morelikely people are working together to obtain benefits simultaneously (Mutual Benefit).Socio-cultural structure of the inherent strength of individuals in masyaraklat Saniangbaka, raisescapital-capital that serves as a unifying and driving force diperantauan Saniangbaka publicwelfare. The networks are formed, shaped its own members as well as networking with membersof other community organizations formally or informally, such as trade and the organization thatserved to increase the welfare of members of the Association saniangbaka citizens.Saniangbaka community social capital also forms of physical capital, human capital, and othercapital-capital:Religion,Language,andTrade.